2015
DOI: 10.1021/jp5116542
|View full text |Cite
|
Sign up to set email alerts
|

Local Electronic Structures and Polarity of ZnO Nanorods Grown on GaN Substrates

Abstract: The polarization and surface reactivity of the ZnO nanorods (NRs) grown on the (0001̅) N-polar GaN substrate and the (0001) Ga-polar GaN substrate by hydrothermal process were studied. We found that the polarization direction of the ZnO NRs grown on the GaN substrates depends on the surface polarity of the GaN growth substrates. The surface planes of ZnO NRs on the Ga-polar GaN substrate and the N-polar GaN substrate are the Zn-polar (positive-charged surface) and the O-polar (negative-charged surface) ZnO sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It is worth noticing that polarity is a bulk crystallographic property and differs from surface termination, namely in that the O- and Zn-polar c -planes can both be O- or Zn-terminated. , The polarity in wurtzite semiconducting compounds such as ZnO and GaN has been extensively investigated. It is known to greatly affect surface stability and configuration, ,,, ,,,, chemical reactivity, , etching behavior, , growth rate, ,,, morphology, , dopant incorporation, as well as electrical and optical properties. , These polarity-dependent properties have so far been almost exclusively determined in the case of ZnO single crystals and epitaxial films. They are still open to a very large extent in the case of ZnO nanostructures including NRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noticing that polarity is a bulk crystallographic property and differs from surface termination, namely in that the O- and Zn-polar c -planes can both be O- or Zn-terminated. , The polarity in wurtzite semiconducting compounds such as ZnO and GaN has been extensively investigated. It is known to greatly affect surface stability and configuration, ,,, ,,,, chemical reactivity, , etching behavior, , growth rate, ,,, morphology, , dopant incorporation, as well as electrical and optical properties. , These polarity-dependent properties have so far been almost exclusively determined in the case of ZnO single crystals and epitaxial films. They are still open to a very large extent in the case of ZnO nanostructures including NRs.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the issue of polarity in the field of ZnO nanostructures have been reported depending on the polarity of the ZnO nucleation surface ,,,, and investigated regarding their polarity itself. The physical and chemical vapor deposition techniques typically results in the formation of Zn-polar ZnO NRs ,,, or nanostructures following the catalyst-free or self-induced approaches, , regardless of the polarity of the nucleation surface.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO has superior advantages such as low cost, facile preparation, morphologic diversity, and high chemical stability. ZnO nanocrystals with different morphologies have some special properties of physics, so intense interests have been devoted to the synthesis of ZnO with various morphologies such as nanowires [10], nanobelts [11], nanorods [12], and nanosheets [13].…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that when the epi-layers have the same polarity as the substrates do, the interfaces are relatively stable. Both interfaces were also speculated by experimental groups [92]. However, they may not be energetically favorable in all cases, because these interfaces can be negatively or positively charged.…”
Section: Ga2o3mentioning
confidence: 82%
“…Next, we considered different interfacial configurations. Experimentally, it is observed that the epitaxial crystal has the same polarity as the substrate without interface modifications and substrate pre-treatment [26,28,92]. Therefore, we first tried all the interface configurations without adlayers.…”
Section: Ga2o3mentioning
confidence: 99%